2018
DOI: 10.1074/jbc.ra118.002405
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of the CD36 receptor reduces visceral fat accumulation and improves insulin resistance in obese mice carrying the BDNF-Val66Met variant

Abstract: Running title: CD36 inhibition improves metabolic dysfunction in obese miceKey words: CD36, diabetes, insulin resistance, obese, salvianolic acid B AbstractObesity-induced metabolic dysfunctions increase risk of vascular diseases including type II diabetes and stroke. While managing obesity is an interest to address the worldwide health problem, how genetic variability affects human obesity development and specific targets for obesity-related metabolic disease have not been thoroughly studied. A single nucleo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
35
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 50 publications
2
35
0
1
Order By: Relevance
“…CD36 expression and signalling are involved in inflammation and disease pathologies. We observed that CD36 expression in adipose T cells was increased in mice fed a western diet (Figure 5(a)), which may have relevance to the findings that associate higher expression of CD36 in adipocytes and adipose tissue macrophages to obesity and inflammation [10][11][12][13][14]. Recent studies have also shown that CD36 expression and fatty acid uptake in cancer cells can be increased by adipocytes and high-fat diet, resulting in significantly enhanced survival and metastases [15][16][17].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…CD36 expression and signalling are involved in inflammation and disease pathologies. We observed that CD36 expression in adipose T cells was increased in mice fed a western diet (Figure 5(a)), which may have relevance to the findings that associate higher expression of CD36 in adipocytes and adipose tissue macrophages to obesity and inflammation [10][11][12][13][14]. Recent studies have also shown that CD36 expression and fatty acid uptake in cancer cells can be increased by adipocytes and high-fat diet, resulting in significantly enhanced survival and metastases [15][16][17].…”
Section: Discussionsupporting
confidence: 68%
“…Expression of CD36 and fatty acid uptake are linked to a number of diseases and pathologies. For example, increased expression of CD36 in adipocytes and adipose tissue macrophages is associated with obesity and inflammation [10][11][12][13][14]. CD36 can be upregulated in cancer cells by adipocytes and high-fat diet to increase fatty acid uptake and promote tumour growth and metastases [15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Yang et al (6) used a unique mouse model containing the human BDNF Val66Met variant and found that, consistent with observations in humans, BDNF M/M mice fed a normal diet had significantly increased body weight relative to BDNF V/V controls by 6 weeks of age. When subsequently fed a high-fat diet for 8 weeks, the BDNF M/M mice became extremely obese with elevated fasting glucose levels and impaired glucose tolerance, implying the development of insulin resistance.…”
mentioning
confidence: 61%
“…CD36 is thought to mediate cross-talk between adipocytes and macrophages in obese mice by facilitating cytokine secretion from macrophages (8). To identify the role of CD36 in the development of obesity in BDNF M/M mice, Yang et al (6) used salvianolic acid B (SAB), a specific CD36 antagonist, in experiments both in vitro and in vivo (9). Although chronic administration of SAB into diet-induced obese (DIO) WT mice had no effect on total body weight during the experimental period (8 weeks), it significantly reduced the accumulation of visceral fat and improved glucose tolerance relative to DIO mice receiving the vehicle.…”
mentioning
confidence: 99%
“…CD36 can influence the response to insulin in a tissue specific manner, as in muscle of mice CD36 deficiency increases insulin sensitivity but, in the liver, it induces insulin resistance, most likely as result of increased cellular fatty acids uptake rather than the presence of fatty acids in plasma (185). In obese mice with elevated CD36 expression due to a polymorphism in the brain-derived neurotrophic factor, inhibition of CD36 by salvianolic acid B improved visceral fat accumulation and insulin resistance (186). These results suggest that by reducing CD36 surface expression and intracellular lipid accumulation, and by modulating the CD36/PI3K/Aktsignaling pathway via hTAP1/SEC14L2 mediated lipid exchange, αT and more so αTP may prevent the development of insulin resistance and excess intracellular lipid accumulation (41,118).…”
Section: Modulation Of Cd36/fat Scavenger Receptor/fatty Acids Transpmentioning
confidence: 99%